Soliton-like solutions supported by refined hydrodynamic-type model of an elastic medium with soft inclusions - Vladimirov, Vsevolod; Skurativskyi, Sergii (Nonlinear Analysis: Modelling and Control, 2024)
A nonlinear elastic medium containing sharp inhomogeneities is considered. The properties of a modified model of such a medium are investigated. The modification consists in including in the asymptotic equation of state those terms that were discarded in the previously considered models. The main purpose of the ongoing research is to analyze the existence, stability, and dynamic properties of soliton-like solutions within the modified model, as well as to compare these solutions with analogous solutions obtained in the previously considered models.
Keywords: nonlocal media model; soliton-like solutions; stability; Evans function; simulation of solitary waves collision